CHANGES IN THE CHOROIDAL THICKNESS AFTER MACULAR BUCKLING IN HIGHLY MYOPIC EYES. Issue 9 (September 2021) - Tang, Ningning; Zhao, Xiujuan; Chen, Jing; Liu, Bingqian; Lu, Lin
Abstract : Purpose: To assess changes in the choroidal thickness (CT) after macular buckling in eyes with high myopia. Methods: Highly myopic eyes that underwent macular buckling surgery were retrospectively analyzed. Data of swept-source optical coherence tomography scanning at baseline and at 1, 3, 6, 12, and 18 months after macular buckling were collected. Subfoveal CT and CT at 750 µ m superior, inferior, nasal, and temporal to the fovea were measured. The total choroidal area, vascular area, and stromal area were measured by the binarization method. The choroidal vascularity index was calculated by dividing the vascular area by the total choroidal area. Results: Forty-one eyes were included in the final analysis. The subfoveal CT increased from 49.85 ± 31.23 µ m preoperatively to 75.74 ± 37.89 µ m 1 month after macular buckling ( P < 0.001), then decreased over time, coinciding with the trends of parafoveal CT, total choroidal area, vascular area, and stromal area. The subfoveal CT was restored to the preoperative level six months postoperatively ( P = 0.202) and remained stable until the end of follow-up. The choroidal vascularity index increased at 1 and 3 months postoperatively ( P = 0.001 and 0.005, respectively). Conclusion: The choroid thickened in the early postoperative period. The compression force of the buckle implant might disturb microcirculatory drainage and contribute to the thickening. The choroid spontaneously recovered to the preoperative level over time. Abstract : Supplemental Digital Content is Available in the Text. The choroid thickened in the early postoperative period after macular buckling. It recovered spontaneously and remained at preoperative levels until 18 months postoperatively. Compression force may be responsible for postoperative choroid thickening.